2008
DOI: 10.4161/auto.5141
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions betweenDrosophila melanogasterAtg1 and paxillin reveal a role for paxillin in autophagosome formation

Abstract: Autophagy is a conserved cellular process of macromolecule recycling that involves vesicle-mediated degradation of cytoplasmic components. Autophagy plays essential roles in normal cell homeostasis and development, the response to stresses such as nutrient starvation, and contributes to disease processes including cancer and neurodegeneration. Although many of the autophagy components identified from genetic screens in yeast are well conserved in higher organisms, the mechanisms by which this process is regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 41 publications
2
60
1
Order By: Relevance
“…Interestingly, it has been reported that vinculin and paxillin are released from FAs during nutrient deprivation. 36 We observed changes in cell morphology in cells plated on collagen I and uncoated substrate when they were incubated in nutrient-free medium. In contrast, no change in cell morphology and in the formation of FAs occurred during incubation in nutrient-free medium in cells plated on collagen IV.…”
Section: Resultsmentioning
confidence: 93%
“…Interestingly, it has been reported that vinculin and paxillin are released from FAs during nutrient deprivation. 36 We observed changes in cell morphology in cells plated on collagen I and uncoated substrate when they were incubated in nutrient-free medium. In contrast, no change in cell morphology and in the formation of FAs occurred during incubation in nutrient-free medium in cells plated on collagen IV.…”
Section: Resultsmentioning
confidence: 93%
“…Another focal adhesion protein essential for autophagy is paxillin. Paxillin interacts with Atg1 in Drosophila (84). Paxillin is a target of YopH which dephosphorylates invasin-induced paxillin to disrupt focal adhesion complexes (85,86).…”
Section: Discussionmentioning
confidence: 99%
“…When we examined MO-injected embryos at different stages of epiboly, there was no difference in the cell shape of the cells on the leading edge of epiboly (data not shown). Actin clumping and disorganization is often a byproduct of cell death ( 73,74 ). Since increased cell death has been reported in many mammalian tissues in response to loss of npc1 function, we examined epiboly-staged embryos for evidence of cell death.…”
Section: Npc1 Morphants That Complete Epiboly Display a Shorter Body mentioning
confidence: 99%